Hubungan Protein Urine dengan Berat Jenis Urine Pada Pasien Gangguan Ginjal - Widianingsih, Agustina (Analis Kesehatan Sains, 2024)
Kidney impairment is a condition where there is a decrease in kidney function. The kidneys filter the blood and excrete metabolic waste through urine. When the kidneys are damaged, the ability of the kidneys to filter blood and excrete waste may decrease. Supporting examination parameters for examining kidney disorders are urinalysis examinations such as Urine Protein and Urine Specific gravity. This study aims to determine the relationship between urine protein and urine specific gravity in patients with kidney disorders. This study was conducted with an analytical observational design with a cross-sectional approach with a sample of 34 samples. The results were tested using the Spearman test. The results showed the highest urine protein level was +4 and the highest urine specific gravity level was 1.005. Spearman test results showed a value of 0.004 (<0.05). There is a relationship between urine protein and urine specific gravity in patients with kidney disorders. Keywords: urine specific gravity, kidney disorders, urine protein